Virtual Reality and Serious Games for Simulating Muscle Force and Joint Torque in Upper Limb Prosthesis Training: A Systematic Literature Review - Camargo, Lisias Carneiro; Lamounier Junior, Edgard Afonso; Soares, Alcimar Barbosa (Anais do Simpósio de Realidade Virtual e Aumentada (SVR), 2025)
This paper presents a systematic literature review on the use of biomechanical models in virtual reality environments, in association with serious games for the training and control of upper-limb prostheses. The review covers studies that integrate musculoskeletal simulations, motion capture, and interaction with virtual systems. The main computational models employed are discussed, along with the motor control strategies adopted. Serious games are considered not only for their motivational role but also as methods for functional assessment in clinical settings. The results indicate a growing interest in the combined use of virtual reality and serious games with biomechanical models, while also revealing a lack of integrated and clinically validated solutions. Notably, no study simultaneously addressed the five criteria defined in this review, namely biomechanical modeling, immersive virtual reality, serious games, force estimation, and joint torque estimation, which highlights a fragmented scenario. This review contributes by presenting an existing gap, as well as proposing a direction for future upper limb prosthesis training systems that are more effective and clinically viable.